The catalytic reduction of nitric oxide over copper doped aluminosilicates - Hwang, Gerard (Department of Chemical Engineering, 2016)
With the object of greater energy efficiency, a role has been identified for a facility capable of the simultaneous removal of NOx, SO₂ and particulates from flue gas at high temperature. This project forms the initial phase of the development of such a high temperature flue gas cleaning facility and is limited to the study of catalytic NOx reduction over aluminosilicates. A copper ion-exchanged zeolite (Cu-ZSM-5) and copper oxide were studied as catalysts for the Selective Catalytic Reduction (SCR) of nitric oxide in the temperature range 250-530⁰ C. Ammonia was employed as the reducing agent. The intention of this investigation was to work towards an examination of the potential for obtaining an active SCR catalyst by doping amorphous aluminosilicate fibres (which are used as high temperature particulate filters), with copper. The direct decomposition of nitric oxide over Cu-ZSM-5 was investigated in order to validate the experimental rig and procedures by duplicating published results. An activation energy of 29 kcal/mol was determined and a reaction order with respect to nitric oxide of 1.2 was obtained at 500⁰ C. Both values compare well with published data. Cu-ZSM-5, CuO supported on silicalite and CuO physically blended with the fibrous aluminosilicate were investigated as SCR catalysts. It was found that: The rate of the SCR reaction was three orders of magnitude higher than the rate of the direct decomposition reaction over Cu-ZSM-5. CuO supported on silicalite yielded higher reaction rates than unsupported CuO and the rates of the former approached those for the reaction over Cu-ZSM-5. An activation energy of 14 kcal/mol was obtained for the SCR reaction over Cu-ZSM-5 and a value of 9 kcal/mol was obtained for reaction over CuO (supported and unsupported). The ability of supported CuO to catalyse the SCR reaction at a rate comparable to that found with Cu-ZSM-5 suggests that the use of CuO should be investigated further, both in its own right as a NOx reducing catalyst since little has been published in this regard, and as a simultaneous NOx/SO₂ removal sorbent/catalyst. The intrinsic catalytic activity of copper oxide and the success with which it has been dispersed/supported on the porous silicalite structure, suggests that a suitably active SCR catalyst form may be obtained if a high dispersion of copper oxide may be achieved on the non-porous aluminosilicate fibres.